Relationship between heart girth, serum progesterone and superovulation response of donor Holstein cows - Abdel-Tawab A. Y. Khalil (Asian Pacific Journal of Reproduction, 2019)
Objective: To determine effects of variations of heart girth, volume trait on embryo quality grade, and to explore the relationship between heart girth and circulating progesterone and correlations of circulating progesterone with embryo quality grade in superstimulated donor Holstein cows. Methods: Nineteen cows were subjected to a standard superstimulation protocol using follicle stimulating hormone. Blood samples were collected before superovulation, at insemination and at collection of embryos for progesterone analysis. Embryo quality grades were compared between high and low heart girth donors. Moreover, Pearson's correlations were determined between heart girth, progesterone and embryo quality. Results: Variation of heart girth was not associated with significant differences in embryo quality grade between high and low heart girth donor cows (P>0.05). However, we observed a significantly higher percentage of the third-grade embryo (24.09%) in low heart girth donors compared to 9.64% in high heart girth donors. Moreover, the percentage of the transferable embryo was numerically higher and that of the degenerated embryo was numerically lower in low heart girth cows. Donor cows with low response to superovulation (total structures ≤ 3) expressed numerically higher mean heart girth, compared to donors with high (total structures >15) and medium (total structures = 4-15) superovulation. Heart girth and body weight of donor cows were moderately correlated (r=0.45, P<0.05), but none was correlated with circulating progesterone at different sampling times except for a moderate correlation between body weight and progesterone at embryo collection (r=0.54, P=0.02). Circulating progesterone before superovulation was moderately correlated to the second-grade embryo (r=0.46, P<0.05) and to the third grade (r=0.52, P<0.05) embryo. Conclusions: Volume traits heart girth may influence the response of Holstein cows to superovulation; however, future studies with a higher number of cows are warranted to clarify significant influences.